Споредбена анализа на екстракциски методи на охратоксин А од животински ткива и нивна селективна примена при квантитативна проценка кај примероци со географско потекло од Р. Македонија - Кучукчакан Николовска, Башак (Факултет за ветеринарна медицина, УКИМ, Скопје, 2018)
Ochratoxin A (OTA) ingested by animal feeds has high affinity for accumulation in pig's kidneys. Consequently, meat products can be a potential contaminating source for human. To our best knowledge, there is no available data for risk assessment of this mycotoxicosis in R. Macedonia. The OTA extraction methods from animal tissues can have significant variations in validation qualifications. The aims of this research were: (1) to make validation assessment on two modified OTA extraction methods of animal tissues - modified liquid-liquid extraction (mLLE) and modified solid-phase extraction (mSPE), and to compare validation qualifications with SPE-IAC (SPE with immunoaffinity column), LLE, SPE-C18; (2) to make qualitative and quantitative assessment of OTA in liver (cattle) and kidney (pig) samples with different geographical origin from the territory of R. Macedonia. Two tissue types (liver and kidney) were used for SPE-IAC with three OTA concentrations (1, 5, и 10 μg/kg), one (kidney) for mLLE with two OTA concentrations (1, 5 μg/kg), LLE (5 μg/kg) and one (liver) for SPE and mSPE C18 with one OTA concertation (5 μg/kg). The qualitative and quantitative analysis was performed with HPLC-FD (high pressure liquid chromatography - fluorescent detector). The extraction methods were assessed according to validation parameters and values described in EU regulative 2002/657/EC: linearity (R2), recovery rate (R, %), limit of detection (LOD, μg/kg), repeatability (RSDr, %) and reproducibility (RSDR, %). For the second aim, liver (cattle) and kidney (pig) samples were collected from three geographical regions of R. Macedonia (central-CMK, western-WMK and eastern Macedonia-EMK), in the period between March, 2014 and February, 2016. OTA extraction was performed with SPE-IAC, while qualitative and quantitative analysis with HPLC-FD. R2 value for LLE was >0,98, whereas >0,99 for all other methods (p<0,05). SPE-IAC (liver) and SPE-IAC (kidney) had R >70%, and mLLE R <70% for ОТА 5 μg/kg (R=67%). These methods had values for RSDr <20% and RSDR <30%. LLE, SPE-C18 and mSPE-C18 methods had R% 25,02%, 15,89% and 5,12%, respectively. From analyzed samples (N=182), 87% had LOD < 0,88 g/ml. The highest values (≥ LOQ) were detected in CMK (pig kidney - 0,63 μg/kg), EMK (cattle liver - 0,97 μg/kg and pig liver - 0,282 μg/kg), WMK (pig liver - 0,364 μg/kg and cattle liver - 0,268 μg/kg). SPE-IAC OTA extraction method in animal tissues was highly compliant with EC 401/2006 regulative (R % =70-110%, RDSr ≤ 20 % and RSDR ≤ 30 %), whereas mLLE was compliant with Codex Alimentarius (R% 60 − 120 % for ОТА concentrations 1−10 μg/kg). The validation assessment of mLLE qualifies this method as alternative, faster and cheaper compared to SPE-IAC. Following the results of OTA analysis in animal tissues from different geographical regions of R. Macedonia, the potential risk of this mycotoxicosis on public health can be excluded.
Compared analysis of extraction methods of Ochratoxin A from animal tissues and their selective application for quantitative assessment in the tissue samples geographically originated from the Republic of Macedonia
Докторска дисертација одбранета во 2018 година на Факултетот за ветеринарна медицина во Скопје, под менторство на проф. д–р Зехра Хајрулаи Муслиу.
Keywords: Ochratoxin A, extraction, animal tissues, HPLC-FD